The Market for Kidneys: Bridging Introductory Courses in Economics and Ethics - Huysmans, Martijn (Journal of Interdisciplinary Studies in Education, 2023)
This article contributes to the literature on interdisciplinary teaching by describing, analyzing, and evaluating an interdisciplinary intervention while students are still gaining disciplinary grounding. The intervention bridges courses in microeconomics and ethics. It focuses on the travelling concepts of voluntariness and value in a potential market for kidneys, and finds that a 15-minute knowledge clip on travelling concepts can help students build interdisciplinary skills. However, an exploratory survey (N=44) also indicates that students in the control group, who watched a clip only on the specific issue at hand, reported a deeper interdisciplinary grasp of that specific topic. Teaching an issue through travelling concepts can hence be seen as an investment in general interdisciplinary skills.